Juvenile Ossifying Fibroma of the Maxilla: A Case Report - Syarifah, NTH; Roselinda, AR; Irfan, M (Bangladesh Journal of Medical Science, 2010)
Juvenile ossifying fibroma (JOF) is an uncommon, benign, bone-forming neoplasm with aggressive local growth that is distinguished from other fibro-osseous lesions primarily by its age of onset, clinical presentation and potential behaviour. We reported a 10 year old girl presenting with a growth in the left upper buccal gingiva which later was diagnosed as juvenile ossifying fibroma. The nature of the disease and outline of management were discussed. Keywords: Ossifying fibroma; Juvenile; Maxilla. DOI: 10.3329/bjms.v9i1.5231 Bangladesh Journal of Medical Science Vol.09 No.1 Jan 2010 49-52